2005
DOI: 10.1152/ajpcell.00505.2004
|View full text |Cite
|
Sign up to set email alerts
|

Renal and intestinal transport defects in Slc26a6-null mice

Abstract: SLC26A6 (PAT1, CFEX) is an anion exchanger that is expressed on the apical membrane of the kidney proximal tubule and the small intestine. Modes of transport mediated by SLC26A6 include Cl−/formate exchange, Cl−/HCO3− exchange, and Cl−/oxalate exchange. To study its role in kidney and intestinal physiology, gene targeting was used to prepare mice lacking Slc26a6. Homozygous mutant Slc26a6−/− mice appeared healthy and exhibited a normal blood pressure, kidney function, and plasma electrolyte profile. In proxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
193
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(210 citation statements)
references
References 41 publications
15
193
1
1
Order By: Relevance
“…The transcellular component of the NaCl reabsorption occurs predominantly through the combined activities of an apical chloride-base exchange mechanism(s) and either a sodium-proton (NHE3) exchange-or sodium-sulfate (NaSi) cotransport-driven base recycling process (2,3). Recent studies suggest that CFEX (SLC26A6, PAT1), a Cl Ϫ -anion exchanger located in the brush border of the proximal tubule, mediates the principal component of the Cl Ϫ -base exchange that is observed in this segment of the nephron (4)(5)(6)(7)(8).…”
Section: Nhe3 ͉ Proximal Tubule ͉ Slc26a6mentioning
confidence: 99%
See 1 more Smart Citation
“…The transcellular component of the NaCl reabsorption occurs predominantly through the combined activities of an apical chloride-base exchange mechanism(s) and either a sodium-proton (NHE3) exchange-or sodium-sulfate (NaSi) cotransport-driven base recycling process (2,3). Recent studies suggest that CFEX (SLC26A6, PAT1), a Cl Ϫ -anion exchanger located in the brush border of the proximal tubule, mediates the principal component of the Cl Ϫ -base exchange that is observed in this segment of the nephron (4)(5)(6)(7)(8).…”
Section: Nhe3 ͉ Proximal Tubule ͉ Slc26a6mentioning
confidence: 99%
“…CFEX has been shown to be capable of mediating multiple anion exchange modes in vitro, including Cl Ϫ -oxalate, Cl Ϫ -HCO 3 Ϫ , Cl Ϫ -formate, and Cl Ϫ -OH Ϫ exchange (5-7), but recent studies with CFEX-null mice suggest that Cl Ϫ -oxalate exchange is the principal Cl Ϫ -anion exchange mode assumed by CFEX in the proximal tubule and that CFEX mediates all of the Cl Ϫ -oxalate exchange that occurs in this segment (8). Therefore, we assessed Cl Ϫ -oxalate exchange activity in isolated BBMV to confirm that the reduction in CFEX protein expression in PDZK1-null mice was associated with a corresponding reduction in CFEX transport activity.…”
Section: The Interaction Of Cfex With Pdzk1 Is Also Mediated Through mentioning
confidence: 99%
“…However, an important function of HCO 3 -secretion in the duodenum is protection of the duodenal epithelium from the acidic chyme delivered from the stomach into the small intestine (Allen and Flemstrom, 2005 of the eutherian duodenum are SLC26A3 and SLC26A6 (Jacob et al, 2002;Singh et al, 2008;Tuo et al, 2006;Walker et al, 2009). However, SLC26A6 contributes little to HCO 3 -secretion (Wang et al, 2005) whereas SLC26A3 is responsible for ~60% of the spontaneous HCO 3 -secretion and ~50% of the cAMP-stimulated secretion, CFTR and a small paracellular leak accounting for the remainder (Walker et al, 2009). It is generally accepted that SLC26A6 is electrogenic (Jiang et al, 2002;Ko et al, 2002;Xie et al, 2002) with an apparent stoichiometry of 1Cl -:2HCO 3 - (Shcheynikov et al, 2006), and early evidence suggested that SLC26A3 was also electrogenic, but with a stoichiometry of 2Cl -:1HCO 3 -, opposite that of SLC26A6 (Ko et al, 2002;Shcheynikov et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we show that H ϩ can alternatively exit across the apical membrane, facilitating luminal HCO 3 absorption. We have demonstrated that all of the JacobsStewart cycle-associated proteins are well expressed in duodenal epithelial cells (3,40) and that cytosolic and membranebound CA activities are essential for luminal H ϩ uptake (27). We now would like to further test the hypothesis that H ϩ , CO 2 , and HCO 3 Ϫ absorption pathways across the apical membrane of duodenal epithelial cells follow the model of the JacobsStewart cycle.…”
Section: Epithelial Hcomentioning
confidence: 92%
“…The two major apical transporters that secrete HCO 3 Ϫ into the duodenal lumen are the cystic fibrosis transmembrane conductance regulator (CFTR) and the apical Cl Ϫ /HCO 3 Ϫ anion exchanger in the SLC26A family (9,40). CFTR plays a major role in the HCO 3 Ϫ secretion stimulated by the cAMP pathway (9).…”
Section: Epithelial Hcomentioning
confidence: 99%